Pengaruh Perceived Ease of Use, Perceived Usefullnes, Attitude Toward Using Technology, Behavioral Intention to use dan Actual technology Use TikTok terhadap Minat Beli Produk fashion di Marketplace Tokopedia - Tri oktavian nurrahman; Ima Amaliah (UNISBA Press, 2024)
Abstract. With current technological developments, all shopping activities can be done online without the need to visit the shop. Along with technological developments in social media, people, including the Millennial Generation, can make purchases online via Tiktok.This research was conducted with the aim of analyzing the influence of Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using Technology, Behavioral Intention to use and Actual technology Use TikTok on Interest in Buying Fashion Products on the Tokopedia Marketplace (Study of the Millennial Generation Group in Bandung City) researchers used quantitative descriptive research. The model used is multiple regression analysis using the Ordinary Least Square (OLS) method. The population in this study is the millennial generation group from Bandung City, totaling 579,994 people, while the sample in this study is 100 millennial generations from Bandung City, taken proportionally from all sub-districts in Bandung City. The sampling technique in this research used stratified random sampling. The test results show that the variables Perceived Ease of Use (X1), Perceived Usefulness (X2), Attitude Toward Using Technology (X3), Behavioral Intention to Use (X4), Actual Technology Use (X5) partially influence the group's buying interest millennials on fashion products on E-commerce Tokopedia. All variables have a relationship direction according to the hypothesis except the attitude variable toward using technology. Abstrak. Dengan perkembangan teknologi saat ini, maka semua kegiatan berbelanja bisa dilakukan online tanpa perlu mendatangi toko tersebut. Seiring dengan perkembangan teknologi dalam media sosial pun Masyarakat termasuk Generasi Milenial bisa melakukan pembelian secara online melalui TiktokPenelitian ini dilakukan dengan tujuan untuk menganalisis pengaruh Perceived Ease of Use, Perceived Usefullnes, Attitude Toward Using Technology, Behavioral Intention to use dan Actual technology Use TikTok Terhadap Minat Beli Produk fashion Di Marketplace Tokopedia (Studi Kelompok Generasi Milenial di Kota Bandung) peneliti menggunakan penelitian deskriptif kuantitatif. Model yang digunakan yaitu analisis regresi berganda dengan menggunakan metode Ordinary Least Square (OLS).. Populasi pada penelitian ini yaitu kelompok generasi milenial Kota Bandung yang berjumlah 579.994 jiwa, sedangkan sampel pada penelitian ini yaitu 100 generasi milenial Kota Bandung yang diambil secara proporsional dari seluruh kecamatan yang ada di Kota Bandung. Teknik pengambilan sampel dalam penelitian ini menggunakan stratified random sampling.Hasil pengujian menunjukkan hasil penelitian bahwa variabel Perceived Ease Of Use(X1), Perceived Usefullnes(X2), Attitude Toward Using Technology(X3), Behavioral Intention to Use(X4), Actual Technology Use(X5) secara parsial berpengaruh terhadap minat beli kelompok milenial atas produk fashion di E-comerce Tokopedia. Semua variabel memiliki arah hubungan sesuai hipotesis kecuali variabel attitude toward using technology.